Computed tomography and cross‐sectional anatomy of the head in the red fox (Vulpes vulpes). (29th April 2020) - Mahdy, Mohamed A. A.; Zayed, Mohammed
Abstract: The red fox ( Vulpes vulpes ) is a universally widespread wild carnivore in the world. It has an important impact on human interests and plays a vital role in conservation biology. There is no report to describe computed tomography (CT) of the red fox head and its correlation with gross anatomy. Therefore, the intent of the present study was to document, by CT, the basic anatomical structures in the head region of the red fox to lay the groundwork of an appropriate anatomical description of the head structures comparable with traditional dissection technique. Three red fox heads were imaged sagittally and transversely using CT scanner. Six red fox heads were then serially cut, sagittally and transversely, by an electric band saw, and the obtained slices were cleaned and photographed. Different anatomical structures on CT images and the corresponding anatomic sections were identified and labelled. CT images revealed an excellent three‐dimensional definition of bony structures of the entire craniofacial region. Moreover, CT scans revealed different contrasts between bones, oral and nasal cavities, paranasal sinuses and pharynx which enabled good visualization of those structures. The paranasal sinus system in red fox was poorly developed and represented by a frontal sinus and a small sphenoid sinus, in addition to a maxillary recess. In conclusion, the series of CT images of the normal red fox head presented in the current study will serve as an anatomical reference for the normal head of the red fox, which in turn will improve knowledge for clinical interpretation.